2017
DOI: 10.1002/jmv.24911
|View full text |Cite
|
Sign up to set email alerts
|

The combination of oseltamivir with azithromycin does not show additional benefits over oseltamivir monotherapy in mice infected with influenza A(H1N1)pdm2009 virus

Abstract: The combination of azithromycin, an immunomodulator, with oseltamivir was compared to oseltamivir monotherapy in a lethal BALB/c model of influenza A(H1N1)pdm09 infection. Groups of 14-16 mice received oral oseltamivir (10 mg/kg once daily for 5 days, starting at day 2 post-inoculation) alone or combined to azithromycin (a single 100 mg/kg dose, injected intraperitoneally at day 3 post-inoculation). Based on survival rates, lung viral titers, and pro-inflammatory cytokine levels, the combination therapy did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, mice displayed less weight loss, less airway inflammation and lower mortality [41]. In contrast, a combination therapy of oseltamivir-azithromycin compared to oseltamivir monotherapy did not provide additional benefits in mice infected with influenza [64]. However, this study had several limitations.…”
Section: Effects On Virus-induced Ardsmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, mice displayed less weight loss, less airway inflammation and lower mortality [41]. In contrast, a combination therapy of oseltamivir-azithromycin compared to oseltamivir monotherapy did not provide additional benefits in mice infected with influenza [64]. However, this study had several limitations.…”
Section: Effects On Virus-induced Ardsmentioning
confidence: 87%
“…First of all, the study designs differed significantly in terms of dosing and treatment duration. FAGE et al [64] only applied a single dose of azithromycin on day 3 post-inoculation. Viral titres were reduced but the combined therapy of azithromycin and oseltamivir did not improve survival probably due to the fact that severe lung injury had already occurred on day 3.…”
Section: Effects On Virus-induced Ardsmentioning
confidence: 99%
“…43 However, the effect was not sustained, and not associated with a change in virus-induced weight loss, a sensitive measurement of influenza pathology. Another study found AZM reduced lung viral titres at day 6 post infection, though the effects were not additive to that achieved with oseltamivir in terms of survival, viral titres or cytokine levels, 46 and so these data remain conflicting. 47 In a separate influenza study, AZM decreased total leukocyte accumulation in lung tissue and BAL, with the largest reduction being in neutrophils, and associated with decreased inflammatory mediators.…”
Section: Mechanism Of Effects In Influenza Amentioning
confidence: 99%
“…44,45 Conversely, Fage C et al concluded that the inclusion of AZI in the combination therapy provided no additional clinical or antiviral benefits over oseltamivir monotherapy in their experimental murine models infected with influenza A. 46 In summary, most experimental and clinical studies investigating the effects of macrolide antibiotics against influenza viruses (mostly type A) were focused on CLA. Even if potential direct and indirect mechanisms by which CLA may works against this virus have been reported, actually the clinical evidence is not strong enough to conclude for any significant medical effect of this antibiotic in flu patients, as summarized in Table 3.…”
Section: Influenza Virusesmentioning
confidence: 99%
“…concluded that the inclusion of AZI in the combination therapy provided no additional clinical or antiviral benefits over oseltamivir monotherapy in their experimental murine models infected with influenza A. 46 …”
Section: Macrolides In Viral Diseasesmentioning
confidence: 99%